Obtenção de novas formas sólidas farmacêuticas e compreensão da sua influência sobre o perfil de dissolução - Vidal, Laura Maria Teodorio (2023)
Within the pharmaceutical field, the application of crystal engineering enables the design of drugs with enhanced properties, such as solubility, dissolution, thermal stability, and flow properties. In view of this subject, one of the main challenges during drug research and development, as well as during the formulation of these products, is to work with the formulation of substances with low water solubility, which directly affects their bioavailability and clinical efficacy. Facing this main issue, this thesis had as one of its objectives to evaluate and discuss how obtaining new solid forms influence the solubility and dissolution of drugs and what is the best data treatment for these types of tests. Furthermore, to evaluate other pharmaceutical properties, time and efforts were dedicated to obtaining previously unreported multicomponent solids of secnidazole and diacerein. Lastly, it was also studied the polymorphism phenomenon of two drug candidate molecules: deoxyartemisinin and riparin. To achieve the proposed objectives of this study, several experimental techniques were used, such as X-ray diffraction, vibrational spectroscopy, thermogravimetry, differential exploratory calorimetry, and ultravioletvisible spectroscopy. Through these techniques, it was possible to elucidate the crystal structure of two pharmaceutical cocrystals: one of benznidazole with oxalic acid and other of secnidazole with carvacrol. Furthermore, it was possible to characterize new solid forms of benznidazole with phenol and secnidazole with thymol. The crystalline structures of -deoxyartemisinin and riparin I were also elucidated. It was also possible to evaluate the relationship of the crystalline structure and the dissolution of riparin’s polymorphs. Through mathematical treatment, it was feasible to remove the error inherent in the loss of volume and mass during the dissolution profile tests, as well as it was possible to improve the data treatment of a salt of ricobendazole using derived spectrophotometry. Finally, it was studied how the formation of cocrystals of benznidazole with oxalic acid and phenol decrease the profile of dissolution of this drug and was determined the theorical pH-dependent solubility of benznidazole cocrystal with oxalic acid.